Influence of drill-string lateral collision on wellbore stability of a horizontal well. (June 2022) - Ma, Tianshou; Huang, Jin; Li, Zhilin; Shi, Yufan; Jia, Lichun; Zhong, Chengxu
A finite element model of wellbore stability was proposed for a horizontal well, and drill-string friction and lateral collision in the process of rotary motion were taken into account. An unconfined compression test was used for model validation, the normalized yielded zone area (NYZA) was employed to analyze wellbore stability, and the influence of a lateral collision on wellbore stability was simulated. The results indicated that the stress-strain curve of numerical simulation consists with unconfined compression test, and the maximum relative error is <2.2%. The evolution of NYZA can be divided into three typical stages: stage I (static balance), stage II (dynamic growth), and stage III (dynamic balance). Both normal and shear stresses reach to the peak value in stage II, while they always fluctuate in a relatively small range in stage III, so that the wellbore stability mainly affected by the first collision of drill-string. Both lateral acceleration and friction effects have significant impact on wellbore stability. The initial collision position and the size of drilling tool have a certain influence on wellbore stability, while the revolving speed of drill-string almost has no impact. The present paper has guiding significance for wellbore collapse prevention and drilling parameter optimization.